Analysis of Cryptic, Systemic Botrytis Infections in Symptomless Hosts - Shaw, Michael W.; Emmanuel, Christy J.; Emilda, Deni; Terhem, Razak B.; Shafia, Aminath; Tsamaidi, Dimitra; Emblow, Mark; van Kan, Jan A. L. (Frontiers in Plant Science, 2016)
Botrytis species are generally considered to be aggressive, necrotrophic plant pathogens. By contrast to this general perception, however, Botrytis species could frequently be isolated from the interior of multiple tissues in apparently healthy hosts of many species. Infection frequencies reached 50% of samples or more, but were commonly less, and cryptic infections were rare or absent in some plant species. Prevalence varied substantially from year to year and from tissue to tissue, but some host species routinely had high prevalence. The same genotype was found to occur throughout a host, representing mycelial spread. B. cinerea and B. pseudocinerea are the species that most commonly occur as cryptic infections, but phylogenetically distant isolates of Botrytis were also detected, one of which does not correspond to previously described species. Sporulation and visible damage occurred only when infected tissues were stressed, or became mature or senescent. There was no evidence of cryptic infection having a deleterious effect on growth of the host, and prevalence was probably greater in plants grown in high light conditions. Isolates from cryptic infections were often capable of causing disease (to varying extents) when spore suspensions were inoculated onto their own host as well as on distinct host species, arguing against co-adaptation between cryptic isolates and their hosts. These data collectively suggest that several Botrytis species, including the most notorious pathogenic species, exist frequently in cryptic form to an extent that has thus far largely been neglected, and do not need to cause disease on healthy hosts in order to complete their life-cycles.